Concrete under arctic conditions - Kivekäs, Lauri; Huovinen, Seppo; Leivo, Markku (VTT Technical Research Centre of Finland, 1985)
In the research, strength and deformation properties of concrete under very wide temperature variations were studied, particularly chances in the compressive strength and modulus of elasticity of various concretes. These chances were studied by testing air-entrained concretes, non-air-entrained concretes and concretes containing hollow plastic microspheres, which were cured under differing moisture conditions at temperatures ranging from +20 °C to -70 °C. The compressive strength increased with rising moisture content and decreasing temperature, whereas the modulus of elasticity harelip chanted with a temperature drop to -20 °C, although it increased at lower temperatures. The freezing strength of concrete was examined using a freezing temperature of -65 °C. In the tests, 5MPa proved to be a safe value of the freezing strength. The frost-resistance of concrete was tested at temperatures ranging from +20 °C to -65 °C. At these temperatures the concretes without air-entrainment suffered damage more rapidly than in tests carried out at temperatures ranging from +20 °C to -20 °C, The air-entrained concretes did not lose their strength, on the other hand the concrete with hollow microspheres and non-air-entrained concretes suffered damage equally early. The hardening of concrete at a temperature of -10 °C and the effect on this of the precuring period, when different anti-freeze admixtures are used, was studied experimentally. The most promising admixture combinations were NaNO2 + Na2SO4, NaNO2 + CaCl2, K2CO3 + a retarder, and Ca(NO3)2 + Na2SO4. Test on hollow-core slabs for cold brittleness at -30 °C were carried out and their complete maintenance of impact ductility was verified.